Electric potential assisted crystallization of lisoleucine in aqueous phase: experimental and computational modelling approach / Nik Salwani Md Azmi - Md Azmi, Nik Salwani (Institute of Graduate Studies, UiTM, 2017)
Crystallization is a major technological process for particle formations. It is important and widely used in the production of pharmaceutical drugs since most drugs particles are produced in crystalline form. L-isoleucine is one of the drugs that exist in crystalline form and it can be produced through crystallization process. However, even slight changes in the crystallization condition can drastically alter crystals properties. Control of the process in order to control the physicochemical properties (solubility, morphology, polymorphism) is crucial to produce the right type of crystal. To overcome this problem, electric potential was applied with the intention to control the process. Hence it has become the main objective of this study to determine the effect of electric potential on solubility and mestastable zone width (MSZW) of L-isoleucine crystallization. Solubility of L-isoleucine experiment was conducted using three different methods; (1) Solubility Method A: Gravimetric method, (2) Solubility Method B: Isothermal dissolution and (3) Solubility Method C: Dissolution with controlled heating rate, while polythermal and isothermal method was adopted for the crystallization process. The results showed that all three methods gave significant difference in solubility data.